Effects of high -intensity interval vs moderate-intensity continous training on the time course adapations in cardiovascular fitness and oxygen uptake kinetics in type 2 diabetes - MCDERMOTT, ADAM DOUGLAS (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2019)
Individuals with type 2 diabetes mellitus (T2DM) present with significant impairments in the dynamic and peak responses of pulmonary oxygen uptake (V̇O2) during exercise. Both low-volume high-intensity interval training (LVHIIT) and moderate-intensity continuous training (MICT) have been shown to be effective at increasing maximal exercise capacity (V̇O2max) in individuals with T2DM, however, the mechanisms and time course of adaptations have not yet been investigated. While MICT has been shown to be effective at accelerating the rate of increase of V̇O2 at the onset of submaximal steady-state exercise (i.e. V̇O2 kinetics), the time course and mechanisms of adaptation are unclear. Furthermore, the effect of LVHIIT on V̇O2 kinetics in T2DM has yet to be investigated. Accordingly, the primary aims of this thesis were to compare the effects of 12 weeks of MICT vs 12 weeks of LVHIIT on the mechanisms and time course of adaptation in a) V̇O2max and b) V̇O2 kinetics to different submaximal exercise transitions in people with uncomplicated T2DM. Three experiments were carried out. Experiment 1 compared the effects of 12 weeks of MICT with LVHIIT on the central and peripheral mechanisms and time course adaptation in V̇O2max in people with uncomplicated T2DM. It was hypothesised that both exercise interventions would improve V̇O2max by inducing changes in central (via increases in cardiac output) and peripheral (via increases in muscle fractional oxygen extraction, estimated using changes in deoxygenated haemoglobin and myoglobin concentration, [HHb+Mb]) mechanisms. Thirty-one participants with T2DM (18 men, mean ± SD, age: 53 ± 9 yr, body mass index: 30.1 ± 4.5 kg.m-2) were randomly assigned to MICT (n = 13, 8 men, 50 min of moderate-intensity cycling), LVHIIT (n = 9, 6 men, 10 x 1 min at ~90% maximal heart rate interspersed by 1 min of ‘unloaded’ cycling) or to a non-exercising control (CON) group (n = 9, 5 men). Exercising groups trained 3 times/week with intensity adjusted every 3 weeks. V̇O2max significantly increased after 3 weeks of MICT (+17%; P < 0.05) and LVHIIT (+8%; P < 0.05) with no further significant changes thereafter (total increases in V̇O2max after 12 weeks of MICT and LVHIIT were 24% and 13% respectively). In terms of central adaptations to training, both MICT and LVHIIT significantly increased peak cardiac output within 3 and 9 weeks of training respectively, with no further changes thereafter. Regarding peripheral adaptations, after 3 weeks of training v there was a significant decrease in the slope of the first linear component of the Δ [HHb+Mb] % vs Δ % peak power output (POpeak) profile (data was curve fitted using a double-linear model) in both the LVHIIT and MICT groups with no further changes observed thereafter, which is indicative of a reduction in the over reliance on O2 extraction due to an improved microvascular O2 delivery. No changes in physical fitness were observed in the CON group. The subsequent 2 experiments focused on the effects of MICT and LVHIIT on the time course and mechanisms of adaptation in V̇O2 kinetics responses during different submaximal exercise transitions in T2DM. Experiment 2 investigated the effects of 12 weeks of MICT and LVHIIT on V̇O2 and muscle deoxygenation ([HHb+Mb]) kinetics during rest to moderate-intensity (80% of each participant’s ventilatory threshold, VT) cycling exercise transitions. A secondary aim was to explore the effects of heavy-intensity (50% Δ, PO equivalent to 50% between the VT and POpeak) ‘priming’ exercise (PE) on subsequent moderate-intensity V̇O2 kinetics responses throughout the exercise training interventions. Unlike the CON group, both LVHIIT and MICT significantly accelerated V̇O2 kinetics after only 3 weeks of training with no further improvements thereafter. In addition, the lack of adjustment in [HHb+Mb] profiles with training resulted in a significant reduction in the ‘overshoot’ of the Δ[HHb+Mb]/ΔV̇O2 ratios observed at baseline in the MICT and LVHIIT groups only, thus, reflecting a superior matching of microvascular O2 delivery to utilisation. At week 0 PE significantly accelerated V̇O2 kinetics and significantly reduced the overshoot of the Δ [HHb + Mb]/ΔV̇O2 ratio during a subsequent bout of moderate-intensity exercise in all groups. However, there was no effect of PE on any of the V̇O2 parameters observed in the LVHIIT and MICT groups beyond 3 weeks of training while the overshoot remained apparent in the control group. This finding further strengthens the evidence that both LVHIIT and MICT improved submaximal exercise capacity by improving the ability of the microvasculature to deliver or redistribute O2 to the exercising muscle resulting in a decreased reliance on O2 extraction for a given workload. Since everyday functional activities involve transitions between exercise intensities, Experiment 3 investigated the effects of 12 weeks of MICT and LVHIIT on V̇O2 and muscle deoxygenation ([HHb+Mb]) kinetics during heavy-intensity (50% Δ) cycling exercise initiated from an elevated baseline (i.e. work-to-work transitions). In addition, as in Experiment 2, the effects of PE on these responses were also assessed. Both LVHIIT and MICT accelerated the overall V̇O2 kinetics response during heavy-intensity exercise after 3 weeks of training through a speeding of the time constant of the primary V̇O2 (τV̇O2P) response and a reduction in amplitude of the slow component (V̇O2SC). The significant reduction in τV̇O2P with MICT and LVHIIT in the presence of an unaltered [HHb + Mb] response profile indicates a likely improvement in O2 delivery; whereas, the significant reduction in the V̇O2SC amplitude after just 3 weeks of MICT and LVHIIT is indicative of exercise induced adaptations in the intrinsic properties of the skeletal muscle and alterations in motor unit recruitment patterns. PE significantly reduced the τV̇O2P as well as V̇O2SC amplitude during a subsequent bout of heavy-intensity exercise initiated from an elevated baseline at week 0 in all groups. However, there was no effect of PE on any of the V̇O2 parameters observed beyond 3 weeks of training only in the LVHIIT and MICT groups. Taken together, the findings of this thesis show that both MICT and LVHIIT improve maximal exercise capacity and accelerate the dynamic response of V̇O2 during rest to moderate and moderate to heavy-intensity submaximal exercise transitions in T2DM by a similar magnitude and within a similar timeframe. Moreover, the reduction in the reliance on O2 extraction during maximal and submaximal exercise indicates that both interventions induced an improvement in peripheral microvascular blood flow that is, at least in part, responsible for the improvements in exercise capacity observed. Importantly, LVHIIT induced these benefits with a time commitment that was more than 50% less than MICT (60 vs. 150 min per week), and given that ‘lack of time’ is consistently presented as one of the primary barriers to exercise participation, it is likely that high-intensity interval training can be an effective intervention to increase exercise adherence rates in people living with T2DM.
APPROVED
Keywords: Exercise; HIIT; VO2 kinetics; muscle deoxygenation; priming exercise; Type 2 diabetes